The Sensing System for the Autonomous Mobile Robot Emmy III - Torres, Claudio Rodrigo [UNESP]; Abe, Jair Minoro; Lambert-Torres, Germano; Silva Filho, Joao Inacio da; IEEE (Ieee, 2011)
This paper shows the results of the sensing system which was designed for the autonomous mobile robot Emmy III. The proposed Sensing System has as its mean part the Paraconsistent Neural Network. This artificial neural network is based on the Paraconsistent Evidential Logics - E tau. The objective of the Sensing System is to inform the other robot components about the obstacle position. The reached results have been satisfactory.
Keywords: Paraconsistent Neural Network; Paraconsistent Logics; Automous Mobile Robot; Sensing System